Textual Analysis: Flex-Working Programs - Sa, Yongjin (Advances in Social Sciences Research Journal, 2018)
<span style="line-height: 115%; font-family: ’Times New Roman’,serif; font-size: 12pt; mso-fareast-font-family: ’맑은 고딕’; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">This study sought to explore how newspaper make sense of the flex-working programs in the Korean government, as well as what the focus of the newspaper articles about the flex-working programs are in terms of its content, terms frequently used, pictures, and headlines. To address, this research conducted a textual analysis based on newspaper articles which cover the flex-working programs derived from two English-language newspapers: The Korea Herald and The Korea Times. As a result, this research confirmed that these two newspapers similarly and mainly focus on problems regarding the current employment environment and work-family balance in Korea, as well as abstract necessities and expected positive outcomes of the flex-working programs. However, coverage in these newspapers did not focus strongly on the provision of detailed guidelines and significant information pertaining directly to use of the flex-working programs. Finally, this study confirmed that the implementation process for flex-working programs may well suffer from weak leadership and political support among public and private employers in the Korean workforce due to the absence of coverage of those critical issues. The other findings and limitations of this study were also specifically discussed.